Efektivitas Model Flipped Classroom Menggunakan Video Pembelajaran Matematika terhadap Pemahaman Konsep - Saputra, M. Eko Arif; Mujib, Mujib (Desimal: Jurnal Matematika, 2018)
Flipped Classroom model is a model where in the learning process is not like in general, that is in the learning process students learn the subject matter at home before the class begins and teaching and learning activities in the class in the form of tasks, discussion about materials or problems that students have not understood. The purpose of this study is to determine the effect of Flipped Classroom model on the ability of understanding mathematical concepts. This research type used Quasi Experiment Design research and sampling technique used is Probability Sampling method with Random Sampling technique. Hypothesis test used in this research is t-test. The result of statistical test shows that the value of t_hitung based on the calculation obtained t_hitung = 12.868, and t_tabel = 1.668 so t_hitung> t_tabel, with a real level of 0.05 in other words it can be concluded that the understanding of mathematical concepts of students who expected model Flipped Classroom is better than the ability to understand concepts that are applied with lecture methods